Facilitating Trade and Structural Adjustment Ecuador Experiences in Non-Member Countries - Duran, Jose (OECD Trade Policy Papers, 2008)
This paper is the second of four country case studies which is a part of a broader research programme addressing trade and structural adjustment issues in non-member economies which was conducted as a follow-up to Trade and Structural Adjustment: Embracing Globalisation (OECD, 2005) which identified policies for successful trade-related structural adjustment. This paper studies the trade liberalisation experience of Ecuador from the 1970s onwards. The report consists of 5 main sections; Section 1 provides the introduction, while section 2 provides an overview of Ecuador?s economic reforms from the 1970s onwards until the 2000s. Section 3 looks at the structural changes in the economy and trade dynamics behind the changes. Section 4 takes a closer look at structural adjustment in four sectors, the cut-flowers, processed tuna, cereals, and textiles and clothing. Section 5 concludes with lessons learnt. Ecuador provides a case of a country whose trade liberalisation and other structural reforms have led to mixed results. While trade liberalisation has improved resource allocations, macroeconomic instability, incomplete reforms, weak institutions and relatively restrictive (but also highly informal) labour markets have made it difficult for Ecuador to reap the full benefits of trade liberalisation